(untitled) (Eurasian Scientific Herald, 2022)
Pomegranate has been grown for the fruit in Uzbekistan since ancient times. The composition of the ripened fruit contains sugar 15-19%, and acid 1.2-2.5%. Pomegranate juice contains iron and a lot of tannin. Pomegranate is used to treat various diseases in medicine. Pomegranate tree is a precious material. Pomegranate is also grown as an ornamental tree.